New Strategies for Social Innovation Market-Based Approaches for Assisting the Poor - Anderson, Steven G. (Columbia University Press, 2014)
Steven G. Anderson is director of the School of Social Work at Michigan State University. His research interests focus on strategies for improving the well-being of the poor. He received a Ph.D. in political science from the University of Michigan and has served as a Fulbright Scholar in China